Muchismo - Cristina de Middel - De Middel, Cristina 1975-; Chiappe, Doménico 1970- (La Fabrica, 2016)
In the work Muchismo, the photographer Cristina de Middel digs around in her studios and brings all of her images to light, exactly the way she has them stored, in colossal, gorgeous chaos, to show them in the exhibition of the same name to be held in June at the Teatro Fernán Gómez in Madrid. This is a sui generis display of her entire oeuvre, with neither a curator nor any apparent order, which seeks to question the art market and its rules. At the same time, the artist is holding another exhibition of the Antipodes series in La Fábrica (Madrid), a series made up of pictures taken in New Zealand in which the artist strives to bring depth back to landscape photography by using mirrors and her own devices. Both works are captured in this publication, a book that had become an object of desire even before it materialised, as always happens with the works of one of the most fascinating photographers on today’s scene.
Exposición/exhibition: "Muchismo", Sala de exposiciones Fernán Gómez, Centro Cultural de la Villa, Madrid: del 1 de junio al 31 de julio de 2016
Keywords: De Middel, Cristina -- 1975-; Cristina de Middel; Fotografie; Neu Seeland; Spanien; Ausstellungskatalog -- Centro Cultural de la Villa de Madrid, Sala de exposiciones Fernán Gómez -- 01.06.2016-31.07.2016 -- Madrid